Influência de variantes genéticas 6 associadas ao gene do receptor TREM-1 no perfil de citocinas e outros 7 mediadores solúveis em indivíduos convalescentes e de fase aguda da COVID - Silva, Wivian da Conceição Costa da (2023)
The relationship between the immune response and COVID-19 has been widely studied, aiming to better understand the immunological mechanisms involved in SARS-CoV-2 infection. We present the Triggering Receptor Expressed on Myeloid Cells 1 (TREM1), which is upregulated in inflammation and is part of an extensive family of immunoglobulin (Ig) receptors discovered in the 2000s. Activation of TREM-1 potentiates inflammation, and some genetic variants in the TREM1 gene have been studied and associated with the worst prognosis in some diseases. In this way, we evaluated the influence of variants in the TREM-1 receptor gene and its association with the profile of soluble mediators, in patients with COVID-19 and convalescent individuals. Variants rs2234237 and rs2234246 were genotyped by qPCR in 138 participants. The measurement of CXCL8, CCL3, CCL2, IL-1β, IL-6, TNF-α and IFN-γ was performed using the Luminex assay. The measurement of sTREM-1, MMP-8 and MMP-2 was performed using the enzyme-linked immunosorbent assay ELISA in 48 participants. Results: The T allele of the rs2234237 variant, mainly in homozygotes, and the C/T genotype of the rs22342346 variant, contribute to the increase in immunological mediators in the study population. The T allele of the rs2234237 variant, mainly in homozygotes, and the C/T genotype of the rs22342346 variants, contribute to the increase in sTREM-1 in the study population. Patients with COVID-19, especially the severe form, with comorbidities and who died, had high levels of CXCL8, CCL3, CCL2, IL-1β, IL-6, TNF-α and IFN-γ. Convalescents from COVID-19 showed a decline in the levels of immune mediators 30 days after clinical cure of SARS-CoV-2 infection. Conclusion: This is the first study to investigate the relationship between variants in the TREM-1 receptor gene and COVID-19 in the Brazilian Amazon. Taken together, our data show that the rs2234237 and rs2234246 variants are not significantly associated with severity and/or mortality in COVID-19. New studies including other variants of the TREM1 gene are necessary to better understand the role of this receptor in the immune system and in modulating the release of immune mediators in response to SARS-CoV-2 infection